2021
DOI: 10.1186/s42836-020-00061-5
|View full text |Cite|
|
Sign up to set email alerts
|

Total knee replacement in Osteogenesis Imperfecta: a case report and review of the literature

Abstract: Background A review of the literature revealed that only 9 total knee replacements were performed on patients with osteogenesis imperfecta (OI), with one being a revision procedure of a periprosthetic fracture. Of the 9 primary procedures, all used cemented prostheses, and 3 patients had an osteotomy at the same procedure. Our patient required a hinged prosthesis because of collateral ligament incompetence and is the first such case reported in the literature. Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…To the best of our knowledge, only 12 total knee replacements in 10 patients with osteogenesis imperfecta and knee osteoarthritis have been reported in the existing literature. 8 , 9 , 14 18 The characteristics of the previously published cases are presented in Table 1 . 8 , 9 , 14 18 One additional case report described a failed hip femoral revision component perforating the femoral trochlea due to poor bone quality that was treated by total femur replacement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, only 12 total knee replacements in 10 patients with osteogenesis imperfecta and knee osteoarthritis have been reported in the existing literature. 8 , 9 , 14 18 The characteristics of the previously published cases are presented in Table 1 . 8 , 9 , 14 18 One additional case report described a failed hip femoral revision component perforating the femoral trochlea due to poor bone quality that was treated by total femur replacement.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 , 14 18 The characteristics of the previously published cases are presented in Table 1 . 8 , 9 , 14 18 One additional case report described a failed hip femoral revision component perforating the femoral trochlea due to poor bone quality that was treated by total femur replacement. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die wenige verfügbare Literatur im Hinblick auf endoprothetische Versorgungen bei Patienten mit OI liest sich insofern auch kritisch und zeigt teils hohe Revisionsraten und vergleichsweise kurz Standzeiten der Implantate [14,16,17,21,22]. In der Erfahrung des Verfassers lassen sich aber bei sorgfältiger präoperativer Vorbereitung unter Einbeziehung der o.g.…”
Section: Osteogenesis Imperfectaunclassified
“…Following publication of the original article [ 1 ], the authors reported an error for some numbers in the sentence “her visual analogue score (VAS) was 3/10, 7/10 and 8/10 before, 6 and 24 months after surgery respectively” in the Case report section.…”
mentioning
confidence: 99%